Digital filmmaking handbook, fourth edition - Schenk, Sonja; Long, Ben. (Boston, MA Cengage Learning, 2011)
Presents a comprehensive filmmaking resource for beginners. This book guides you from your initial concept to your finished project, covering writing, pre-production planning, shooting, how to create professional level shots and effects, and post-production editing and effects.
Keywords: Digital cinematography -- Handbooks, manuals, etc; Digital video -- Handbooks, manuals, etc; Video recording -- Data processing -- Handbooks, manuals, etc